2020
DOI: 10.1111/jre.12743
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association between obesity and gingivitis among 12‐year‐old South Brazilian schoolchildren

Abstract: ObjectiveTo assess the association between weight status and gingivitis in a representative sample of 12‐year‐old schoolchildren from South Brazil.BackgroundAn association between obesity and gingivitis in children and adolescents has been observed; however, the present evidence has major limitations.MethodsA cross‐sectional study was conducted in Porto Alegre, South Brazil, from September 2009 to December 2010 and included a representative sample of 1528 12‐year‐old schoolchildren attending public and private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Furuta et al suggested that sex-based differences in gingivitis in young people could be explained by oral health behaviours and hygiene statuses because females had greater knowledge, a more positive attitude, a healthier lifestyle, and better oral health behaviours than males [ 17 ]. In contrast, Lock et al reported that girls had a markedly higher prevalence of gingivitis than boys, especially among obese girls [ 33 ]. Differences between genders could be partly attributed to the regulatory effect of sex steroid hormones on gingival physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Furuta et al suggested that sex-based differences in gingivitis in young people could be explained by oral health behaviours and hygiene statuses because females had greater knowledge, a more positive attitude, a healthier lifestyle, and better oral health behaviours than males [ 17 ]. In contrast, Lock et al reported that girls had a markedly higher prevalence of gingivitis than boys, especially among obese girls [ 33 ]. Differences between genders could be partly attributed to the regulatory effect of sex steroid hormones on gingival physiology.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the mother can be an important font of transmission in children especially in the first two years of life, when Streptococci mutans are initially transferred, especially using dental materials [3,[33][34][35][36]. us, if the mother does not follow appropriate behaviour of oral hygiene [27][28][29][30][31], the risk of development of cavities in the child increases since the concentration of bacteria is higher and more aggressive [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, children experiencing overweight or obesity are more likely to develop dental caries [ 157 ]. Obese schoolchildren have been shown to be more likely to develop gingivitis than their normal-weight counterparts, whereas this relationship is modified by gender [ 158 ]. It was demonstrated that girls suffering from obesity tend to have a higher likelihood of gingivitis; however, no such relationship was observed among boys [ 158 ].…”
Section: Non-metabolic Complications Of Obesity In Childrenmentioning
confidence: 99%